Comparison of Forwarding Mechanism Between IPv4 and Named Data Networking (NDN) Case Study: Network Congestion - Brada Sentosa, Renaldy; Wisaksono Sudiharto, Dodi; Herutomo, Anton (International Journal of Engineering and Technology, 2019)
A routing mechanism which is used by Internet Protocol version 4 (IPv4) is stateful and adaptive. It updates and chooses the best candidate of several routes based on its routing table information. Nonetheless, its forwarding mechanism is stateless, because it just forwards packets to routerâ€™s neighborhood based on information in its routing table called as Routing Information Base (RIB). Indeed, if there is a network congestion, and the RIB is still not update, its forwarding mechanism cannot find an alternate link. There is a different mechanism, namely Named Data Networking (NDN). It is a content-oriented network architecture. Packets which are sent only bring Name of data exchanged and do not include their IP addresses. A consumer is going to request in the form of Interest packets to a nearest node. The neighborhood router can manage several Interest packets if their status are still pending. This status management is part of NDN forwarding mechanism and provides an advantage which NDN based router can measure performance of multiple paths and also can use alternative ones if there is a network congestion, although its RIB has still not been updated. This mechanism can be achieved by comparing an arrival time of Interest packet with an arrival time of Data packet (Satisfied Interest). Yet, the change from IP network architecture into NDN network architecture requires substantial requirements. Upgrading hardware and software can be very expensive, but it is not necessarily provides a clear advantage. Surely, it is too risky. To reduce that risk, simulations are created to compare a performance of both network architectures. This research describes how NDN forwarding mechanism can find alternate paths and also uses a multipath forwarding mechanism when a network congestion happened compared with IP based forwarding mechanism. This research is based on network simulations and gives an explanation that NDN network architecture, especially its forwarding mechanism gives more advantages than the other one.Â Â